Problemas para iniciar una investigación previa al juicio antes y durante la pandemia Covid-19. Comparación con el contexto internacional - Larysa Arkusha; Oleksandr Torbas; Vladlena Voloshyna; Viktor Zavtur; Tetiana Babchynska (Ius Humani. Jornal do direito, 2020)
The challenges posed by the spread of coronavirus infection are global and affect almost all spheres of public life, including criminal justice. To minimize direct social communication, the possibilities of using remote legal procedures in criminal proceedings have been expanded. The legal procedure of pre-trial proceedings established in the Criminal Procedure Code in the part of the beginning of the pre-trial investigation turned out to be misfit to the conditions of continuous quarantine. The purpose of the article is to identify, describe and propose solutions to the problems of starting a pre-trial investigation during the Covid-19 pandemic. Thus, to solve this problem, the article examines the existing problems of pre-trial investigation before and during the Covid-19 pandemic, taking into account domestic scientific experience, as well as current foreign practices to resolve this issue to study the possibility of adopting their best practices and implementing them in the legislation. In the process of research, such methods as the dialectical, structural-functional analysis, comparative-legal and historical method. It is necessary to emphasize the simplification of the procedure for reporting the detected signs of criminal offenses, which necessitates raising the professional level of law enforcement officers, as well as conducting large-scale information work among internet users.